Morphological and molecular data reveal Retiboletus cyanescens sp. nov. and the new subgenus Nigroretiboletorum (Boletaceae) - Li, Jin; Wang, Zhen; Liu, En-De; Yang, Zhu L.; Li, Yan-Chun (Phytotaxa, 2022)
Relationships between species of Retiboletus were inferred from morphology and nucleotide sequences of the translation elongation factor 1-α gene (tef1-α), the second largest subunit of RNA polymerase II (rpb2), the nuclear ribosomal large subunit (nrLSU), and the nuclear ribosomal internal transcribed spacer (ITS), based on Maximum Likelihood and Bayesian analyses. Our analyses indicated that the genus Retiboletus is divided into two major clades, with at least 10 species-level lineages in China. Accordingly, we describe a new subgenus, i.e. R. subg. Nigroretiboletorum, and a new species R. cyanescens of this subgenus. The newly proposed subgenus accommodates R. griseus and its allied taxa characterized by grayish white, white, or grayish pink hymenophores and white to gray context in pileus. Color pictures of fresh basidiomata and line drawings of the new species are provided, with a discussion concerning its taxonomic and phylogenetic relationships within the genus. In addition, a key to the species of Retiboletus in China is provided.